Effects of forest patch size on butterflies in urban forest - Mohd Joni, Anis Liyana (2018)
Habitat destruction caused by urbanization can lead to fragmentation of forests. With the loss of habitats, the biodiversity in these habitats will also become threatened. One of the taxa that has been threatened by habitat loss is butterfly. This study investigated the abundance and species richness of butterfly within fragmented urban forests in the state of Selangor and their relation to size of forest patch. These forests were Ayer Hitam Forest Reserve (AHFR), Bangi Forest Reserve (BFR), Bukit Cerakah Forest Reserve (BCFR) and Sungai Lalang Forest Reserve (SLFR). Point count transect was used to collect the data. Thirty sampling points using systematic sampling with a random start were established at all four study sites. The AHFR had the highest butterfly abundance and species richness. The reason for this was because the size of the AHFR was bigger compared to the other two forest patches and the distance of the AHFR was relatively close to the SLFR. However, more research should be done on the biodiversity of these forest patches and butterflies in urban areas.